Risk factors associated with response to highly active antiretroviral therapy after 24 months of administration to HIV, HIV/HBV and HCV patients in Kumba Health District, South West Region of Cameroon - Adamu Ndongho Ndifontiayong; Innocent Mbulli Ali; Jean Baptiste Sokoudjou; Karimo Ousenu; Jerimiah Ndimumeh Mbogwe; Ousenu Karimo; Christopher Bonglavnyuy Tume (Archives of Clinical Gastroenterology - Peertechz Publications, 2022)
Hepatitis B (HBV) and C (HCV) are two other forms of infections for which co-infection in HIV has been associated with alteration of the immune response,  increased risk of progression to liver diseases, and increased risk of hepatotoxicity associated with antiretroviral therapy. This study aimed to establish the prevalence of hepatitis B surface antigen (HBsAg) and hepatitis C antibody (HCVAb) among HIV patients, evaluate response to treatment between the different categories and identify the possible risk factors associated with this burden of hepatitis B/C among HIV patients and the resulting responses to HAART in Kumba Health, in the South West Region of Cameroon. Method: We performed a systematic screening using Rapid Diagnostic Test, for HBsAg and HCVAb among 299 HIV patients enrolled at the treatment centers in Kumba Health District (District hospital Kumba, Kumba Town Sub-Divisional hospital, and the Apostolic hospital Banga Bakundu), with all positives for HBV or HCV confirmed by the ELISA and results analyzed using SPSS version 20. Out of the 299 participants, 52 HIV patients, 36 HIV/HBV, and 12 HIV/HCV patients were involved in the prospective cohort study for 24 months which permitted monitored the immune response (CD4 counts and viral load test), as well as variation of biochemical parameters (ALAT/ASAT, albumin, bilirubine, creatinine) and weights of the studied participants.  Result: Out of the 100 HIV patients involved in the prospective cohort, 36 and 12 were hepatitis B and C virus-positive respectively. Following the analysis of the viral load and CD4 cell counts, there were differences in response to HAART after 24 months between the mono-infected and co-infected patients, taking into consideration the, CD4 cell counts (HIV: 930.846 cells/mm3, HIV/HBV: 595.139 cells/mm3 and HIV/HCV: 678.500cells/mm3), and viral load (HIV: 1777.85copies/ml, HIV/HBV: 2232.61copies/ml and HIV/HCV: 750.83copies/ml).  There were variations in biomarkers of the liver (ALAT/ASAT, bilirubin, and albumine) and renal function (creatinine) for both patients. There were also variations of the different biomarkers linked to the infection status of the different participants.   Conclusion: There were positive variations in viral load and CD4 cell counts among the studied participants, with a more rapid response to the mono-infected HIV patients compared to the co-infected patients. Similar strength was observed in the variation of the different biomarkers and such variation indicates that co-infection of HIV patients with either hepatitis B or C virus can affect rapid response to HAART and the variations in the level of Biochemical markers among the different categories are linked to the alteration of the functions of the respective organs and so this result could be used for health decisions regarding co-infections.